ANALISIS TINGKAT KESEJAHTERAAN EKONOMI PETANI BERDASARKAN PENDAPATAN USAHATANI PEPAYA CALIFORNIA (Carica papaya L.) DI MUANG DALAM KELURAHAN LEMPAKE KECAMATAN SAMARINDA UTARA (Analysis of Economic Prosperity Level of Farmer Based on Income of California Papaya Farming (Carica papaya L.) in Muang Dalam Lempake Urban Village North Samarinda Subcity) - FACHRI AMNAN; SYARIFAH MARYAM; SYARIFAH AIDA (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2019)
Income level influences on economic prosperity of farmer. The purpose of this research was to know prosperity level of farmer income based on income of papaya california farming in Muang Dalam, Lempake Urban Village, North Samarinda Subcity. The research was done from June to December 2017. The sampling method were census method. Data collection was done through survey or observation and interviews. Data was analyzed to know total cost,  revenue, and income. Income was divided by the number of family members to know income per year, then it was compared with City Minimum Salary (CMS) as a prosperity index. The results of research show that farmer income from california papaya farming as much as IDR8,647,495.92 month-1 respondent-1 for an average planting area of 0.92 ha. CMS in Samarinda City the year 2017  as much as IDR2,442,180.62 month-1. The average of farmer income from papaya california farming IDR2,189,034.33 capita-1 month-1. If it was compared with the data of Statistics of East Kalimantan the year 2016 as much as IDR510,041.00 month-1 for rural area, the prosperity level of california papaya farmer is at a level of wealth or above the poverty line.